Energy efficient multiejector CO2 cooling system for high ambient temperature. (1st October 2020) - Singh, Simarpreet; Maiya, Prakash M.; Hafner, Armin; Banasiak, Krzysztof; Neksa, Petter
Highlights: A novel CO2 cooling system with ejector in series configuration is experimentally evaluated for Indian supermarket application at high ambient temperature. Maximum enhancement in COP and reduction in PIR of the CO2 cooling system with IHX is 7.2% and 6.2% respectively and maximum pressure lift obtained is 5.9 bar. Flooding/non-flooding conditions for the evaporator is experimentally evaluated and the maximum superheat at MT evaporator is reduced by 84%, which results in 6.51% reduction in PIR. Abstract: Experimental evaluation of a multiejector CO2 cooling system of 33 kW cooling capacity is conducted for an Indian supermarket at high ambient temperature context. The test-rig is designed to depict the actual supermarket cooling requirements in India with three different cooling temperature levels simultaneously; freezing, medium refrigeration and air-conditioning. The rig is equipped with a novel design consisting of two multiejectors; low ejection ratio ejector (LERE) and high ejection ratio ejector (HERE), in a series configuration. It is observed that the maximum pressure lift of 5.5 bar is obtained with this new design. Moreover, improvement in the overall system performance with the support of the internal heat exchanger (IHX) is evaluated. Enhancements observed in the maximum COP and PIR are 7.2% and 6.2% respectively. Furthermore, the test-rig performance with the flooding and non-flooding of the medium temperature evaporator (refrigeration) is evaluated. It is observed that the evaporator flooding reduces its superheat at the exit by 83.84%, leading to the overall reduction of PIR by 6.51%. The performance of the proposed system is also compared with the reported field data obtained at a low ambient temperature context. The results projected that the proposed cooling system with series multiejector configuration is a reliable choice for higher ambient temperatures and it is expected to outperform the existing systems at lower ambient temperatures.